Gêneros digitais e docência: uma experiência colaborativa de formação de professoras de Língua Portuguesa com foco no letramento digital - Carolina Duarte Garcia (2023)
According to Fairclough (2003), the development of genres, which are ways to discursively act and interact, occurs simultaneously with the development of technologies. Thus, learning and mastering them is important to inter(act) considering the technologization and virtualization of sociodiscursive practices. If, on the one hand, digital literacy practices at school should be taken into consideration by teachers, on the other hand, those teachers should be offered opportunities of initial and continuing education to assimilate digital technologies. Stemming from these considerations, this research aimed, in general, to investigate the relationship of a group of Portuguese language teachers with digital technologies whey working with digital genres in their pedagogical practices before and during the Covid-19 pandemic. In this research, Freirian pedagogy (FREIRE, (2011 [1997]), critical theories on texts and discursive genres (FAIRCLOUGH, 2003; MAGALHÃES, 2017), studies about Digital Literacy (COSCARELLI, 2017; RIBEIRO, 2019; 2021; COSCARELLI; RIBEIRO, 2021), concerning teaching practices during the social isolation caused by the pandemic (BUNZEN, 2020; COSCARELLI, 2020; JUNQUEIRA, 2020; COSCARELLI; RIBEIRO, 2023), as well as Brazil’s National Common Curricular Base (BNCC) (BRASIL, 2018) were fundamental This research, of applied nature, with qualitative approach, and essentially defined as interpretative and interventionist, was characterized by the action research method, since it proposed an action of reflective continuing teacher education, consisted of four meetings and with the collaboration of five teachers, where topics concerning digital literacy were discussed, and teaching materials were collaboratively analyzed and created. The reports produced by the five teachers during the meetings were transcribed and then categorized, systematized, and analyzed using the Atlas.ti software. The data analysis revealed that the collaborators integrate and wish more efficiently to integrate digital genres and platforms into their practices, but face challenges, such as the lack of access to internet and digital equipment in their own schools and in students' homes, as well as the absence of continuing teacher education on digital technologies. Such challenges escalated during the pandemic, a time when the collaborators had to reorganize themselves to teach. The analysis also showed that the action of continuing teacher education and the collaborative production of an activity were motivating for that group of teachers. Hence, this research reveals the need for interactive and formative spaces where educators can, together, rethink their own activities and practices. In addition, it highlights the urgency of fairer and more egalitarian public policies for access to digital technologies and the Internet in Brazilian public schools.